STUDY OF THE AIRCRAFT CONICAL FAIRING DYNAMIC BEHAVIOUR UNDER COMBINED OF TEMPERATURE AND FORCE LOADING - I. K. Turkin; D. A. Rogov (Научный вестник МГТУ ГА)
The article deals with the dynamic behavior of the unevenly heated thin-walled conical shell of revolution of the aircraft fairing type under the loading conditions by shock wave in the gaseous environment, approximated by travelling load. The displacements of the shell, resulting from the preliminary uneven heating, are determined from the solution of the equations of thermoelastic equilibrium. Solution of the dynamic problem consists of the integration of the nonlinear equations of shell motion at the assigned initial displacement, zero initial velocities and boundary conditions, corresponding to the fastening of fairing. As a result of the solution of the presented problem the amplitudes of the fluctuations of the fairing nose edge are determined. It allows to determine the stress-strained state of shell for the purposes of the determination of its bearing capacity.